Behavior of Thai Tourists Visiting in Cultural Attraction in Community-based of Bangkok - Jatturat, Pitsamai; Na-Talang , Chawalee (Dusit Thani College Journal, 2022)
The purpose of this study were 1) to study the behavior of Thai tourists visiting in cultural attraction in Community-based of Bangkok, and 2) to study the relationship between demographic characteristics and tourist behaviors of Thai tourists visiting in cultural attraction in community-based of Bangkok. This research was quantitative research, involving the collection of data through questionnaires with 400 participants. The analysis method is descriptive statistics : frequency, percentage, and Chi-squared test with a significance of 0.05. The results found that the behavior of Thai tourists visiting in cultural attraction in Community-based of Bangkok were as follows : It was found that most of them came with family and relatives. Weekend Trips Travel frequency less than 3 months/ 1 time using vehicles to travel by private car. Spend less than 2,000 baht. On travel with the purpose of recreational travel, second to see archaeological sites and antiquities, and to spend free time with family members equal to experience the community lifestyle. Get to know community attractions from Facebook, second only to website media, and from YouTube. The most interesting forms of cultural tourism are archaeological sites and museums. Secondly, interested in the traditional architectural style and interested in the style of shopping, apparel, etc. Food & Souvenirs. The results of the chi-squared test identified that gender is related with expenditure on travel. Age is related with the mode of travel and the kind of vehicle used for traveling. Status is related with the mode of travel, the time of year in which travel occurs, the kind of vehicle used for traveling and expenditure on travel. The level of education is related with the vehicle used for travel. Career is related with the mode of travel, the number of visits, the vehicle used for travel and expenditure on travel. Moreover average monthly income is related with the mode of travel, the time of year in which travel occurs, the kind of vehicle used for travel, and expenditure on travel at a significance of 0.05